An ecofeminist position in critical practice: Challenging corporate truth in the Anthropocene. Issue 6 (11th July 2022) - Barthold, Charles; Bevan, David; Corvellec, Hervé
Abstract: Drawing on selected discourses of non‐essentialist ecofeminism, this article proposes and substantiates an ecofeminist position. This distinct position is shown to bring with it a capacity to challenge widely uncontested, corporate‐produced truths regarding the benefits and the legitimacy of certain commercial activities. Three historical cases inform the discussion: the fights led by Rachel Carson against dichlorodiphenyltrichloroethane, by Erin Brockovich against hexavalent chromium, and by Vandana Shiva against genetically modified organisms. Distinguishing characteristics of this emblematically individual and critical activist practice include that it is aimed at fighting environmental degradations; it originates from outrage; it is sustained by dedication and courage; and it combines pedagogy, politics, and ethics. We show how this practice may be understood by reference to acknowledged ecofeminist tenets and in particular with the advocating of a holistic, respectful association with all forms of life on Earth. This is in stark contradistinction to dualist, corporate positions of self‐interested detachment from the environment, and a corresponding denial of the entanglement of the social and physical worlds. We show how such an ecofeminist position has been capable of disrupting both established corporate truths and the discursive power relationships attached to them; and how it engenders an imperative that corporations must confront and engage with the deliberate, anthropogenic consequences of their activities.